Analysis of the efficiency and influencing factors of the urban and rural residents social endowment insurance in China: from the perspective of regional heterogeneity - Dai, Aibi; Hu, Yuanbo; Xie, Henglang; Zhao, Wei; Keskin, Burak (Frontiers in Public Health, 2025)
IntroductionChina’s urban and rural residents social endowment insurance (URRSEI) plays a key role in ensuring the quality of life of the older adult and promoting social stability.MethodsBased on the data of 31 provinces in China from 2012 to 2022, this study evaluates the efficiency of URRSEI and analyzes its influencing factors through DEA method and Tobit Model.Results and discussionThe overall efficiency of China is high. Eastern region has the highest efficiency. The efficiency of central region is relatively stable. Western region has the lowest average efficiency. The level of local fiscal social security expenditure is negatively correlated with efficiency, while the increase of institutional maintenance rate and educational resources significantly improves the performance of URRSEI. The urban registered unemployment rate and the number of unemployment insurance recipients play a positive role in the security function.